Art and human rights contemporary Asian contexts - Turner, Caroline; Webb, Jen (Rethinking Art's Histories, 2016)
Contemporary Asian art has had a remarkable impact on global art practice, in addition to serving as a record of the region's history from decolonisation to the present. Many Asian artists are deeply concerned about what it means to be human and to contribute to the development of a sustainable society, as well as having a sustained commitment to making art.